Infiltrating regulatory T cells promote invasiveness of liver cancer cells via inducing epithelial-mesenchymal transition - Huang, Ai-Hua; Wang, Hong-Bo; Wu, Zhi-Feng; Wang, Yi-Hong; Hu, Bo; Jiang, Zhi-Nong; Jin, Mei; Wang, Lin-Bo; Gao, Ya-Bo (Translational Cancer Research, 2019)
Background: Regulatory T (Treg) cells are a major component of the microenvironment of hepatocellular carcinoma (HCC) contributing to immunosuppression. The present study aimed to evaluate the effects of Treg cells on the invasion potential of HCC. Methods: Infiltrating Treg cells were isolated from fresh HCC tissues by immunomagnetic bead separation and detected by flow cytometry. Circulating tumor cells (CTCs) were detected using the CellSearch platform. The cell migration and invasion potentials were evaluated by Transwell assays. The cell viability was tested by the cell counting kit-8 (CCK8) approach, and the apoptosis rates were determined by flow cytometry. The concentrations of active transforming growth factor-β1 (TGFβ1) were measured by enzyme-linked immunosorbent assay. Results: Infiltrating Treg cells significantly correlated with the number of CTCs and vascular invasion (both P